Sailing Through the Literary Genres - Bello, Carlos; Ramírez, José (CIEX JOURNAL, 2019)
Genres are an essential part in the creation of materials, they are regularly used to define the theme of movies, series, novels, etc., but the important part of a genre is attracting attention and keeping the audience interested in the material and mostly if the material changes continually. Through time one of the main problems which remain in language learning is to maintain the student’s attention, that for, it is important that teaching material must be attractive, interactive and meaningful. One of the proposals from the following work is to catch and maintain the attention by means of these materials, which are assigned considering the following: Contextualized materials, to allude to student’s identity, adaptability of the materials, changing if the genre to generate curiosity and surprise among the student.